Critical Essays in Appalachian Life & Culture - Simon, Rick (Appalachian State University, 1982)
The proceedings from the 1982 Appalachian Studies Conference, edited by Rick Simon, Grace Edwards, Ron Eller, Joan Moser, and Barry M. Buxton, includes contributions by Rick Simon; Ronald D. Eller; Deborah Morentz Markley and Brady J. Deaton; William W. Philliber and Phillip J. Obermiller; Virginia McCoy Watkins and Diana Gullet Trevino; Grace Toney Edwards; Harold Branam; Parks Lanier; Joan Moser; Melinda Bollar Wagner; and Thomas Plaut.